Contingência organizacional e mensuração de desempenho: um estudo em ONGs brasileiras - Oliveira, Alan Santos de (2017)
The general objective of the study was to investigate the relations of contingency factors with the practices related to the measurement of performance in the scope of Brazilian NonGovernmental Organizations (NGOs). For that, a correspondence survey was used, based on the researches of Ferreira and Otley (2009) and Wadongo (2014), with 43 organizations listed in the Brazilian Association of Nongovernmental Organizations (ABONG). For the operationalization of the research questionnaire, variables were subdivided into three fundamental blocks: the first one aimed at demography; the second specifying the contingency factors in NGOs and the third highlighted the performance variables. The data were treated using descriptive statistics and the Spearman correlation coefficient. The main results of the study revealed the particular influence that the profile of the managers and presidents of the NGOs can exert in the use of practices of measurement of performance. Organizational determinants, represented by internal contingency factors, were the main attributes that were directly associated with practices related to performance measurement in Brazilian NGOs. The external environment of NGOs had little influence on the adoption and use of managerial practices. In addition, strong positive correlations were identified between planning and performance measurement practices with the use of management control systems. This research can contribute to the specific literature on managerial accounting and the business market of the third sector by identifying characteristics that are not well explored, such as the profile of managers and presidents of NGOs, contingency factors and management practices used in the sector, The influence of situational factors in the use of practices regarding the measurement of performance in NGOs.